Strategic Action Over Theory and Talk: How to Enact a Better Future - Dale, Michael; Service, Robert W.; Loudon, David L. (Journal of Strategic Innovation and Sustainability, 2020)
Many have perceived the need for agility in future-proofing workforces as globally disruptive technologies reshape work (Saran, 2018). Eason, et al, comprehensively addressed the teaching and learning components of these reshaped strategic imperatives (2019). Now with Covid-19 realities, the necessity to show ‘how’ to manage, lead and do strategy in order to stress that critical concept of ‘innovative adaptation’ has hit hard. Saran’s warning has collided with 2020 shocks to demand the current research question: ‘How can academicians and practitioners assure workforces can have sustainable strategic success given the new deeply embedded, yet ever changing competitive, ecological and global imperatives?’